Essência do queijo artesanal: desafios para manutenção das territorialidades dos pequenos produtores de queijo canastra em São João Batista da Serra da Canastra, distrito de São Roque de Minas/MG - Giácomo, Leonardo (2022)
The presente dissertation has as its central objective to understand the territorial dynamics of the producers, through the cultural relations established by the families, expressed in the know-how of Queijo Canastra at the district of São João Batista da Serra da Canastra, municipality of São Roque de Minas/MG. To this end, a qualitative approach was developed, with principles of Cultural Geography and Geoethnography. Based on the theoretical framework, based mainly on the concepts of territory/territoriality, we understand the object of the research involved in the discussions on agri-food systems and reflections about the criteria established for the production of artisanal foods in the country, with regard to quality. Furthermore, it presents Queijo Canastra as food, that is, it points out the multiple dimensions that involve the act of eating, or the commensality, by presenting the biodiversity of cheeses and inserting the research object from the perspective of Food Systems, raising the cultural aspects, especially in the relations of cheese with the state of Minas Gerais. Also, the spatial scope of research in the regional historical process is contextualized and addresses an important territorial component, nature, through the presentation of the landscapes that make up the territories and the changes caused by the creation of the Serra da Canastra National Park. Finally, we sought to identify in the customs and traditions, the aspects that make up the know-how of the families surveyed.